2014
DOI: 10.1631/jzus.b1300156
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast proliferation alters cardiac excitation conduction and contraction: a computational study

Abstract: Abstract:In this study, the effects of cardiac fibroblast proliferation on cardiac electric excitation conduction and mechanical contraction were investigated using a proposed integrated myocardial-fibroblastic electromechanical model. At the cellular level, models of the human ventricular myocyte and fibroblast were modified to incorporate a model of cardiac mechanical contraction and cooperativity mechanisms. Cellular electromechanical coupling was realized with a calcium buffer. At the tissue level, electri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 58 publications
2
12
1
Order By: Relevance
“…Preliminary experiments [28] showed that hiPSC-CF increase the contraction displacement of the tissue constructs with increasing RFC of up to 50%. This is inconsistent with the computational study of Zhan et al, [23] which suggested that the active stress (and thus the contraction displacement) of ventricular CMs decreases when fibroblasts are added to the tissue. However, it should be noted that their model was not validated with experiments and the results should therefore be treated with caution.…”
contrasting
confidence: 89%
“…Preliminary experiments [28] showed that hiPSC-CF increase the contraction displacement of the tissue constructs with increasing RFC of up to 50%. This is inconsistent with the computational study of Zhan et al, [23] which suggested that the active stress (and thus the contraction displacement) of ventricular CMs decreases when fibroblasts are added to the tissue. However, it should be noted that their model was not validated with experiments and the results should therefore be treated with caution.…”
contrasting
confidence: 89%
“…1 for details). In particular, this model was used as the electrical component in electromechanical models combined with different mechanical modules [22,23,33].…”
Section: Tp + M Modelmentioning
confidence: 99%
“…A tissue-level hallmark of HF is increased fibrosis and proliferation of cardiac fibroblasts. Several in vitro studies and mathematical modeling studies have documented that electrical coupling between myocytes and fibroblasts will lead to changes in APD and intracellular Ca 2+ ( Zhan et al, 2014 ; Li et al, 2017 ). Experimental evidence suggesting the formation of gap junctions between myocytes and fibroblasts in vitro ( Gaudesius et al, 2003 ) has focused researchers attention on the altered electrophysiological properties of myocytes due to this intercellular coupling to explain conduction abnormalities and reentries ( Miragoli et al, 2006 ; Xie et al, 2009a ; Majumder et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%